Increasing Prayer Ability for Children in Cibeber Village, Sukagumiwang District, Indramayu Regency - Iko Rizqonah; Ibnudin; Ahmad Syathori (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Prayer is a type of worship in the Islamic religion carried out by Muslims. Prayer is used as the main form of worship that influences the faith and quality of a Muslim's worship. Performing prayer is obligatory for all Muslims. So one form of student contribution in growing the quality of society is by participating in community service activities in Cibeber Village.